Biologia czy kultura mózgu. W poszukiwaniu uwarunkowań działalności edukacyjnej - Michalak, Renata (Kultura-Społeczeństwo-Edukacja, 2016)
An unusual flowering neuroscience is perceived in many scientific areas and education also. The scientific disciplines such as neuropedagogic, neuroteaching or neuroprogramming are trying to use the data of neuroscience in optimizing educational process for children, teenagers, and adults. Improving the functions of human brain and maintaining its cognitive capacity are very important and attractive activities for both researchers and practitioners of education, now. However, it will not be possible without a good knowledge of the basics and the determinants of development of brain. This article presents neurobiological and cultural context of programming of educational process.